2014
DOI: 10.1101/lm.035105.114
|View full text |Cite
|
Sign up to set email alerts
|

NMDA receptor- and ERK-dependent histone methylation changes in the lateral amygdala bidirectionally regulate fear memory formation

Abstract: It is well established that fear memory formation requires de novo gene transcription in the amygdala. We provide evidence that epigenetic mechanisms in the form of histone lysine methylation in the lateral amygdala (LA) are regulated by NMDA receptor (NMDAR) signaling and involved in gene transcription changes necessary for fear memory consolidation. Here we found increases in histone H3 lysine 9 dimethylation (H3K9me2) levels in the LA at 1 h following auditory fear conditioning, which continued to be tempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 68 publications
3
48
1
2
Order By: Relevance
“…DNA methylation generally decreases transcriptional access to DNA, although the functional effects of this gene silencing depend on the genes that are altered. As indicated previously, NMDAR activity drives regulation of LSD1, and its activation reduces LSD1 [18] transcription, indicating a greater extent of DNA methylation and correlation with its cofactor CoREST, which participates in the activation complex of histone methylation by LSD1.…”
Section: Introductionsupporting
confidence: 60%
“…DNA methylation generally decreases transcriptional access to DNA, although the functional effects of this gene silencing depend on the genes that are altered. As indicated previously, NMDAR activity drives regulation of LSD1, and its activation reduces LSD1 [18] transcription, indicating a greater extent of DNA methylation and correlation with its cofactor CoREST, which participates in the activation complex of histone methylation by LSD1.…”
Section: Introductionsupporting
confidence: 60%
“…Additionally, transgenic mice overexpressing the chimeric subunit with the GluN2B aminoterminal domain and the GluN2A carboxy-terminal domain demonstrated impaired long-term social recognition and olfactory recognition memory, similar to what was previously described in the transgenic GluN2A overexpression mice . The NMDA receptor is highly expressed in the forebrain areas (Hestrin 1992b;Monyer et al 1994;Sheng et al 1994) and has been shown to be necessary in the formation of memory Gao et al 2010;Gupta-Agarwal et al 2014) and the consolidation of long-term memory (Shimizu et al 2000;Santini et al 2001;Roesler et al 2005;Wu et al 2007;Liu et al 2014). While social memory is a different form of memory involving different mechanisms than olfactory memory, several of the same brain areas are involved in both types of memory.…”
Section: Discussionmentioning
confidence: 99%
“…In the LA, H3K9me2 levels were increased one hour following auditory fear conditioning and this increase persisted until twenty-five hours following behavioral training. In contrast, H3K4me3 remained unchanged in the LA following training (Gupta-Agarwal et al, 2014).…”
Section: H3k9 Methylation In Learning and Memorymentioning
confidence: 86%